Chemical Characterization, Antioxidant and Antimicrobial Properties of Different Types of Tissue of Cedrus brevifolia Henry Extracts - Despina Charalambous; Nicolas-George Homer Eliades; Michalis Christoforou; Eleni Kakouri; Charalabos Kanakis; Petros A. Tarantilis; Maria Pantelidou (Molecules, 2022)
This study aimed to determine the chemical composition of different types of tissue of Cedrus brevifolia Henry (Pinaceae) methanolic extracts, namely needles, twigs, branches, and bark. Cedrus brevifolia is a narrow endemic coniferous tree species of Cyprus, growing in a sole population in the mountainous area of Paphos Forest. Chemical analysis of the extracts was performed using liquid chromatography combined with time-of-flight high-resolution mass spectrometry (LC/Q-TOF/HRMS). The majority of the 36 compounds tentatively identified belonged to the flavonoids family. The extract of needles was the richest extract in terms of secondary metabolites. The extracts were studied for their antioxidant activity using the DPPH free radical scavenging assay. Additionally, the antibacterial activity was evaluated by determining both the minimum inhibitory concentration and the minimum bactericidal concentration against Staphylococcus aureus and Escherichia coli. All extracts demonstrated antioxidant property, while bark gave the highest antioxidant capacity (IC50 value of 0.011 mg/mL) compared to the other tissues. Antibacterial activity was observed against both types of bacteria, with the extract of branches presenting the strongest activity against S. aureus (MIC, 0.097 mg/mL and MBC, 0.195 mg/mL). This is the first time that extracts of needles, twigs, branches, and bark of C. brevifolia are compared regarding their chemical composition as well as their antimicrobial and antioxidant properties.